Tusklessness amongst the Queen Elizabeth National Park elephants, Uganda - Eve Abe (Pachyderm)
Only the abstract and a summary of the presentation and following discussion are published. The level of tusklessness in Queen Elizabeth elephants was examined to try and find out if there had been selective offtake of tusked individuals, and to determine the increase of the level of tusklessness. Previously tusklessness in the population was very rare as exemplified by records such as the fact that only 1 animal out of 2000 shot in 1920 was tuskless. The present study showed 10% of females are tuskless, 9.5% of the females are single-tusked, and 9.5% of the males are tuskless. Two-thirds of the elephant over 40 are tuskless but no young males less than 10 years old are tuskless. There appears to be a strong genetic basis for tusklessness with 21 of the families studied 42.8% were tusked, 28.6% tuskless and 23% being mixed tusked/tuskless. Future work may include biopsy analysis to identify a possible genetic basis.